Un voyage d’oscar Milosz en Lituanie: tentative de retrouvailles - Dručkutė, Genovaitė (Literatūra, 2018)
[full article and abstract in French; abstract in English and Lithuanian] Oscar Milosz, poète et écrivain français d’origine lituanienne, de 1920 à 1925 occupait le poste de Chargé d’Affaires de Lituanie en France et en tant que diplomate se rendit plusieurs fois en Lituanie. L’objet de cet article est le récit d’un voyage de Milosz en Lituanie, au cours du mois d‘août de 1922, en compagnie de Maurice Prozor, comme lui d’origine lituanienne, et de sa fille. Ce voyage est raconté par Greta Prozor, témoin oculaire. Le but de l’article est d’analyser le récit en faisant attention à quelques points : 1. l’image de Lituanie, telle qu’elle surgit au cours de la narration,2. la figure de Milosz comme son protagoniste. Summary The article analyzes the story of Oskaras Milašius’s journey to Lithuania which took place in August 1922. Accompanied by her father Maurice Prozor, the author of the story Greta Prozor is also the one who traveled alongside the poet and witnessed his journey first hand. As the analysis draws on the theoretical grounding for travel writing, the article seeks to define and interpret both the image of Lithuania and the figure of the protagonist of the story Milašius. The analysis comes to the conclusion that the author of the story reflectively foregrounds the geographical, historical, social, and cultural history of the country unknown to her before. It also comes to the realization that the “otherness” of Lithuania and its inherent “exotics” lie within the union between the past and the present. It is the union between the past full of life and the present times that determines the distinctive singularity of Lithuania in Europe, which the travelers seem to know well. During the cause of the story, the figure of Milašius is defined through the literary character of Don Quixote, the poet’s alter ego. His nostalgia-driven attempt at the reunion with the family’s past is, in fact, impossible; it cannot be accomplished in present reality. The real reunion with the past most yearned for is possible only throughout the oral and written story.